Inovasi dan Rekonstruksi Undang-Undang Sektoral Daerah untuk Desentralisasi Asimetris - Failaq, Muhammad RM Fayasy; Madjid, Mario Agritama SW (Research and Development Agency Ministry of Home Affairs, 2023)
Decentralization, which was voiced louder after the reform, in fact, still leaves residue. Among them are the uniformity of decentralization and the desire for federalism which has always existed but is challenging to execute. On this basis, the right solution is through asymmetric decentralization, which currently applies to special autonomous regions and does not solve the above problems. For this reason, this research seeks to examine the proper concept of asymmetric decentralization and present a solution in the form of regional sectoral law innovations. This research is a normative juridical law research with a conceptual approach. The data were obtained from secondary data with various legal materials related to the theme. Furthermore, the authors analyzed these data qualitatively to produce objective conclusions. In conclusion, asymmetric decentralization can also be applied to non-special autonomous regions with specific geographical, economic, administrative, and cultural aspects as basic reasons. The entrance does not need to be amended because it is enough to reconstruct regional sectoral laws and innovate to add specific government affairs.